Analisis Efisiensi Perbankan Syariah Di IndonesiaDengan Menggunakan Metode NonparametrikData Envelopment Analysis (DEA) - Ismunarsih, Yuning Tyas; , Dr. Anton Agus Setiawan, SE, M.Si (2017)
ABSTRACTION This study aims to measure the efficiency of Perbankan Sharia in Indonesia in 2015. In this research using DEA (Data Envelopment Analysis) with the frontier approach that VRS (Variable Return to Scale). The data used is secondary data obtained through an annual financial report issued by the bank. The technique used for sampling is purposive sampling, the sample used is 5 Islamic Bank in Indonesia. This research there are three input variables, namely Assets, Deposits, and BTK, variable output consists of Operating Income and Financing. Results from this study is the 5th Islamic Bank who has researched the Bank experiencing inefficient ie BRIS Bank (92.08%). The rest of the 4 other Bank has already reached the level of 100% efficient. Keywords: Islamic Banking, Efficiency, Data Envelopment Analysis.